Sex Differences in Health Behaviors of Austrian Teachers and School Principals - Derrick R. Tanous; Mohamad Motevalli; Katharina Wirnitzer (International Journal of Population Data Science, 2022)
Introduction Currently, about 2% of the European working population (~5 million people) are teachers, who are a characterized occupational group with various roles as educators, partners, counselors, social directors, professional managers, and political theorists. Teachers’ health has a remarkable effect on teaching quality, and consequently, on the success of students of future generations. Public and occupational health are highly related to lifestyle behaviors (including diet type and PA); however, little is known regarding lifestyle patterns in different groups of teachers, particularly males and females. This study aimed to investigate sex differences in health/lifestyle behaviors of Austrian secondary-level teachers and school principals.